Low-loss iron-nickel magnetic powder core composite coating method
By surface treatment and silica coating of iron and nickel, mixed in proportion, and coated with epoxy modified silicone resin, the problems of high loss and low magnetic permeability in high-frequency applications are solved, and the iron-nickel magnetic powder core with low loss and high magnetic permeability are achieved.
Patent Information
- Application Number
- CN202111408930.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-24
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-11-24
AI Technical Summary
Existing metal magnetic powder cores have problems of high loss and low magnetic permeability in high-frequency applications, which is difficult to meet the demand for high-frequency performance of electronic devices.
By surface treatment of iron and nickel, coated with silica, then mixing the two in proportion, and coated with epoxy modified silicone resin to form a uniform, thermally stable insulating film, thereby improving the resistivity and heat resistance of the magnetic powder core.
The low loss and high permeability characteristics of the iron-nickel magnetic powder core are achieved, and the frequency stability and thermal stability are improved.
Smart Images

Figure BDA0003373224590000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal soft magnetic materials, and in particular relates to a low-loss iron-nickel magnetic powder core composite coating method. Background Art
[0002] Iron-nickel powder core is a metal powder core made of alloy powder of Fe and Ni. The powder core can work under high power, high DC bias or high frequency AC. It is mainly used in switching regulation inductors, online noise filters, flyback transformers, power factor correction and pulse transformers.
[0003] At present, metal magnetic powder cores are mainly obtained by mixing metal magnetic powder and insulating materials evenly, coating the surface of the magnetic powder with a uniform and dense insulating material, and then pressing and forming it and then undergoing a certain heat treatment. However, the power loss of the magnetic powder core is closely related to the type and amount of the coated insulating material and the coating method. With the development of high-frequency electronic equipment, it is a necessary trend to require metal magnetic powder cores to have excellent properties such as high magnetic permeability and low loss. Therefore, it is worth studying how to obtain low-loss magnetic powder cores by improving the coating method. Summary of the invention
[0004] The purpose of the present invention is to provide a low-loss iron-nickel magnetic powder core composite coating method. The coating method comprises the following steps: surface-treating iron and nickel respectively and then coating them with silicon dioxide, then mixing the two in proportion, and coating them with epoxy-modified silicone resin. The coating is uniform and has good thermal stability. The obtained iron-nickel magnetic powder core has the characteristics of low magnetic loss and high magnetic permeability.
[0005] To achieve the above object, the present invention provides a low-loss iron-nickel magnetic powder core composite coating method, comprising the following specific steps:
[0006] S1. The iron ingot and the nickel ingot were placed in a medium frequency induction furnace for smelting, and after impurities were removed, the powder was crushed by spraying, and then sieved according to the particle size of 150-300 mesh for standby use;
[0007] S2 were weighed 50-55 parts by weight of iron powder and 45-50 parts by weight of nickel powder in S1 were separately surface treated, and then were placed in a blender and mixed with 1-1.5 parts by weight of silica, stirred for 1-2h, to obtain a surface coated with silica iron-coated powder and nickel-coated powder;
[0008] S3. The iron-coated powder and nickel-coated powder S2 were mixed, and then 3-4 parts by weight of epoxy-modified silicone resin mixed solution was added, stirred, and dried to obtain an insulating iron-nickel magnetic powder;
[0009] S4. After adding lubricant to the insulating iron-nickel magnetic powder coated in S3, the powder was placed in an automatic dry powder molding hydraulic press, and the molding pressure was 18-24t / cm2, and the pressure was maintained for 2-4s to form a blank magnetic powder core;
[0010] S5. The blank magnetic powder core formed in S4 is heat treated at 600-700° C. for 2-3 hours under nitrogen protection to obtain an iron-nickel magnetic powder core.
[0011] In the technical solution, iron powder and nickel powder are mixed with high heat-resistant silicon dioxide respectively to form iron-coated powder and nickel-coated powder with a thin layer of surface coating. The addition of silicon can improve the fluidity of iron and nickel, make the mixing more uniform, and at the same time improve the heat resistance and corrosion resistance, and increase the resistivity. Then the two are mixed, and epoxy-modified silicone resin is added to coat a uniform insulating film on the surface of the iron-nickel magnetic powder, which further increases the resistivity, reduces the magnetic loss, and improves the frequency stability.
[0012] Furthermore, in the above technical solution S1, after the impurities are removed, the sulfur content in the iron is less than 0.01%.
[0013] Too high sulfur content in iron powder will reduce its magnetic permeability and saturation magnetic flux density, while increasing hysteresis loss and coercivity. In this technical solution, the content of sulfur in iron powder is reduced to below 0.01% by using impurity removal method, which is beneficial to improve magnetic permeability and reduce magnetic loss.
[0014] Furthermore, in the above-mentioned technology S2, the particle size of the silicon dioxide is less than 300 mesh, and the stirring speed is 300-500r / min.
[0015] In the technical solution, the particle size of silicon dioxide is controlled to be smaller than that of iron powder and nickel powder, so as to facilitate the formation of silicon dioxide film on the surface of iron powder and nickel powder, thereby improving resistivity and heat resistance.
[0016] Furthermore, in the above technical solution S2, the surface treatment method is: add 0.03-0.04% of phosphorus pentoxide to the iron powder or nickel powder, grind for 1-2 hours, and then add 10-50 times the weight of the phosphorus powder, respectively, and react for 0.5-1 hour to obtain. Specifically, the hot water is hot water with a temperature of 80-100°C. In this technical solution, a small amount of phosphorus pentoxide is first added to the iron powder or nickel powder and mixed and ground, which can improve its resistivity and strength, reduce eddy current loss, and improve the efficiency of the grinding ball. After adding hot water, the excess phosphorus pentoxide can be added to water to form phosphoric acid, forming a passivation layer on the surface of the iron powder and nickel powder to reduce magnetic loss.
[0017] Furthermore, in the above technical solution S3, the mixed solution of the epoxy-modified silicone resin is obtained by adding 20-40 parts by weight of mica powder, 20-50 parts of silicon powder and 0-50 parts of titanium dioxide to 100 parts by weight of the epoxy-modified silicone resin, and grinding the mixed solution with a grinder for 1-2 hours.
[0018] In the technical solution, mica powder has good elasticity, insulation, high temperature resistance and strong adhesion. It is added to the resin as an additive to improve the insulation, mechanical and high temperature resistance of the resin. Silica powder is quartz powder with an average particle size of 0.1-0.3μm, which has excellent electrical insulation and wettability, can eliminate the internal stress of the resin, and improve the insulation and arc resistance of the resin. Titanium dioxide, as an inorganic filler, can improve the heat resistance and mechanical strength of the resin, has good surface wettability and is easy to disperse.
[0019] Furthermore, in the above technical solution, the solid content of the epoxy-modified silicone resin is 52-58%.
[0020] Furthermore, in the above technical solution, the epoxy-modified silicone resin is obtained by mixing E-20 epoxy resin and dimethyldiethoxysilane in a weight ratio of 1:0.3-0.5. Specifically, 1 part by weight of E-20 epoxy resin and 0.3-0.5 parts by weight of dimethyldiethoxysilane are added to cyclohexanone or butyl acetate solvent and a catalyst, and the mixture is heated in a stirrer for a reaction of 2-3 hours and then cooled to obtain the obtained resin.
[0021] Furthermore, in the above technical solution S4, the lubricant is one of zinc stearate or amide wax, and the usage amount accounts for 0.4-0.8% of the total amount of the insulating coated iron-nickel magnetic powder.
[0022] The present invention has the following beneficial effects:
[0023] 1. The present invention can improve magnetic permeability and reduce magnetic loss by strictly controlling the sulfur content in the raw materials;
[0024] 2. The present invention increases the phosphorus content in the raw material through surface treatment, thereby increasing the resistivity and strength and reducing the eddy current loss;
[0025] 3. The present invention improves resistivity and heat resistance by surface treating iron and nickel respectively and then coating them with silicon dioxide, then mixing the two in proportion and coating them with epoxy-modified silicone resin solution. The coating is uniform and has good thermal stability. The obtained iron-nickel magnetic powder core has the characteristics of low loss and high magnetic permeability. DETAILED DESCRIPTION
[0026] The experimental methods in the following examples are conventional methods unless otherwise specified. The raw materials involved in the following examples are common commercial products and can be purchased from the market unless otherwise specified.
[0027] The present invention is described in further detail below in conjunction with embodiments:
[0028] Example 1
[0029] A low-loss iron-nickel magnetic powder core composite coating method comprises the following specific steps:
[0030] S1. The iron ingot and the nickel ingot are placed in a medium frequency induction furnace for smelting. After impurities are removed, the sulfur content in the iron is less than 0.01%. The powder is crushed by spraying and then sieved according to a particle size of 200 mesh for standby use;
[0031] S2. Weigh 50 parts by weight of iron powder in S1, add 0.02 parts by weight of phosphorus pentoxide, grind for 1 hour, then add 1 part by weight of 80°C hot water, react for 1 hour, put it in a blender and mix it with 1 part by weight of silicon dioxide with a particle size of less than 300 mesh, and stir it at a speed of 300r / min for 2 hours to obtain an iron-coated powder with a surface coated with silicon dioxide; weigh 50 parts by weight of nickel powder, add 0.02 parts by weight of phosphorus pentoxide, grind for 1 hour, then add 1 times the weight of phosphorus powder at 80°C hot water, react for 1 hour, put it in a blender and mix it with 1 part by weight of silicon dioxide with a particle size of less than 300 mesh, and stir it at a speed of 300r / min for 2 hours to obtain a nickel-coated powder with a surface coated with silicon dioxide;
[0032] S3. The iron-coated powder and nickel-coated powder S2 were mixed, and then 3 parts by weight of the epoxy-modified silicone resin mixed solution was added, stirred, and dried to obtain an insulating iron-nickel magnetic powder;
[0033] S4. Add 0.5 parts by weight of zinc stearate to the insulating iron-nickel magnetic powder in S3 and place it in an automatic dry powder molding hydraulic press at a molding pressure of 18t / cm 2 Under the condition of , the pressure is maintained for 4s to make the blank magnetic powder core;
[0034] S5. The blank magnetic powder core formed in S4 is heat-treated at 600°C for 3 hours under nitrogen protection to obtain an iron-nickel magnetic powder core.
[0035] The mixed solution of epoxy-modified silicone resin is prepared by adding 100 parts by weight of epoxy-modified silicone resin, 20 parts by weight of mica powder, 30 parts of silicon powder and 20 parts of titanium dioxide, and grinding the mixed solution for 1 hour using a grinder.
[0036] Example 2
[0037] A low-loss iron-nickel magnetic powder core composite coating method comprises the following specific steps:
[0038] S1. The iron ingot and the nickel ingot are placed in a medium frequency induction furnace for smelting. After impurities are removed, the sulfur content in the iron is less than 0.01%. The powder is crushed by spraying and then sieved according to a particle size of 250 mesh for standby use;
[0039] S2. Weigh 52 parts by weight of iron powder in S1, add 0.016 parts by weight of phosphorus pentoxide, grind for 1.5 hours, then add 0.8 parts by weight of 90°C hot water, react for 0.8 hours, put into a blender and mix with 1.2 parts by weight of silicon dioxide having a particle size of less than 300 mesh, and stir at a speed of 400r / min for 1.5 hours to obtain an iron-coated powder having a surface coated with silicon dioxide; weigh 48 parts by weight of nickel powder, add 0.015 parts by weight of phosphorus pentoxide, grind for 1.5 hours, then add 0.75 parts by weight of 90°C hot water, react for 0.8 hours, put into a blender and mix with 1.2 parts by weight of silicon dioxide having a particle size of less than 300 mesh, and stir at a speed of 400r / min for 1.5 hours to obtain a nickel-coated powder having a surface coated with silicon dioxide;
[0040] S3. The iron-coated powder and nickel-coated powder S2 were mixed, and then 3.5 parts by weight of the epoxy-modified silicone resin mixed solution was added, stirred, and dried to obtain an insulating iron-nickel magnetic powder;
[0041] S4. Add 0.6 parts by weight of amide wax to the iron-nickel magnetic powder coated in S3 and place it in an automatic dry powder molding hydraulic press at a molding pressure of 20t / cm 2 Under the condition of , the pressure is maintained for 3s to make the blank magnetic powder core;
[0042] S5. The blank magnetic powder core formed in S4 is heat treated at 650° C. for 2.5 h under nitrogen protection to obtain an iron-nickel magnetic powder core.
[0043] The mixed solution of epoxy-modified silicone resin is prepared by adding 30 parts by weight of mica powder, 30 parts of silicon powder and 20 parts of titanium dioxide to 100 parts by weight of epoxy-modified silicone resin, and grinding the mixed solution for 1.5 hours using a grinder.
[0044] Example 3
[0045] A low-loss iron-nickel magnetic powder core composite coating method comprises the following specific steps:
[0046] S1. The iron ingot and the nickel ingot are placed in a medium frequency induction furnace for smelting. After impurities are removed, the sulfur content in the iron is less than 0.01%. The powder is crushed by spraying and then sieved according to a particle size of 300 mesh for standby use;
[0047] S2. Weigh 55 parts by weight of iron powder in S1, add 0.02 parts by weight of phosphorus pentoxide, grind for 2 hours, then add 1 part by weight of 100°C hot water, react for 0.5 hours, put into a blender and mix with 1.5 parts by weight of silicon dioxide having a particle size of less than 300 mesh, and stir at a speed of 500 r / min for 1 hour to obtain an iron-coated powder having a surface coated with silicon dioxide; weigh 45 parts by weight of nickel powder, add 0.018 parts of phosphorus pentoxide, grind for 2 hours, then add 0.9 parts by weight of 100°C hot water, react for 0.5 hours, put into a blender and mix with 1.5 parts by weight of silicon dioxide having a particle size of less than 300 mesh, and stir at a speed of 500 r / min for 1 hour to obtain a nickel-coated powder having a surface coated with silicon dioxide;
[0048] S3. The iron-coated powder and nickel-coated powder S2 were mixed, and then 4 parts by weight of the epoxy-modified silicone resin mixed solution was added, stirred, and dried to obtain an insulating iron-nickel magnetic powder;
[0049] S4. Add 0.8 parts by weight of zinc stearate to the insulating iron-nickel magnetic powder in S3 and place it in an automatic dry powder molding hydraulic press at a molding pressure of 24t / cm 2 Under the condition of , the pressure is maintained for 2s to make the blank magnetic powder core;
[0050] S5. The blank magnetic powder core formed in S4 is heat treated at 700°C for 2 hours under nitrogen protection to obtain an iron-nickel magnetic powder core.
[0051] The mixed solution of epoxy-modified silicone resin is prepared by adding 40 parts by weight of mica powder, 20 parts of silicon powder and 10 parts of titanium dioxide to 100 parts by weight of epoxy-modified silicone resin, and grinding the mixed solution for 1-2 hours using a grinder.
[0052] Comparative Example 1
[0053] A low-loss iron-nickel magnetic powder core composite coating method, the specific steps are the same as those of Example 1, except that the sulfur content in the iron is higher than 0.04%.
[0054] Comparative Example 2
[0055] A low-loss iron-nickel magnetic powder core composite coating method comprises the following specific steps:
[0056] S1. The iron ingot and the nickel ingot are placed in a medium frequency induction furnace for smelting. After impurities are removed, the sulfur content in the iron is less than 0.01%. The powder is crushed by spraying and then sieved according to a particle size of 200 mesh for standby use;
[0057] S2 weighed 50 parts by weight of iron powder and 50 parts by weight of nickel powder in S1 and mixed evenly, then added 3 parts by weight of epoxy-modified silicone resin mixed solution, stirred evenly, and dried to obtain an insulating iron-nickel magnetic powder;
[0058] S3. Add 0.5 parts by weight of zinc stearate to the insulating iron-nickel magnetic powder in S2 and place it in an automatic dry powder molding hydraulic press at a molding pressure of 18t / cm 2 Under the condition of , the pressure is maintained for 4s to make the blank magnetic powder core;
[0059] S4. The blank magnetic powder core formed in S3 is heat-treated at 600°C for 3 hours under nitrogen protection to obtain an iron-nickel magnetic powder core.
[0060] The mixed solution of epoxy-modified silicone resin is prepared by adding 100 parts by weight of epoxy-modified silicone resin, 20 parts by weight of mica powder, 30 parts of silicon powder and 20 parts of titanium dioxide, and grinding the mixed solution for 1 hour using a grinder.
[0061] Comparative Example 3
[0062] A low-loss iron-nickel magnetic powder core composite coating method comprises the following specific steps:
[0063] S1. The iron ingot and the nickel ingot are placed in a medium frequency induction furnace for smelting. After impurities are removed, the sulfur content in the iron is less than 0.01%. The powder is crushed by spraying and then sieved according to a particle size of 200 mesh for standby use;
[0064] S2. Weigh 50 parts by weight of iron powder and 50 parts by weight of nickel powder in S1 and mix them evenly, add 0.04 parts by weight of phosphorus pentoxide, grind for 1h, then add 1 times the weight of phosphorus powder at 80°C hot water, react for 1h, put into a stirrer and mix with 2 parts by weight of silicon dioxide having a particle size of less than 300 mesh, and stir at a speed of 300r / min for 2h to obtain an iron-nickel coated powder coated with silicon dioxide on the surface;
[0065] S3. The iron-nickel coated powder in S2 was added 3 parts by weight of an epoxy-modified silicone resin mixed solution, stirred and dried to obtain an insulating iron-nickel magnetic powder;
[0066] S4. Add 0.5 parts by weight of zinc stearate to the insulating iron-nickel magnetic powder in S3 and place it in an automatic dry powder molding hydraulic press at a molding pressure of 18t / cm 2 Under the condition of , the pressure is maintained for 4s to make the blank magnetic powder core;
[0067] S5. The blank magnetic powder core formed in S4 is heat treated at 600°C for 3 hours under nitrogen protection to obtain an iron-nickel magnetic powder core.
[0068] Comparative Example 4
[0069] A low-loss iron-nickel magnetic powder core composite coating method comprises the following specific steps:
[0070] S1. The iron ingot and the nickel ingot are placed in a medium frequency induction furnace for smelting. After impurities are removed, the sulfur content in the iron is less than 0.01%. The powder is crushed by spraying and then sieved according to a particle size of 200 mesh for standby use;
[0071] S2. Weigh 50 parts by weight of iron powder in S1, add 0.02 parts by weight of phosphorus pentoxide, grind for 1 hour, then add 1 part by weight of 80°C hot water, react for 1 hour, put it in a blender and mix it with 1 part by weight of silicon dioxide with a particle size of less than 300 mesh, and stir it at a speed of 300r / min for 2 hours to obtain an iron-coated powder with a surface coated with silicon dioxide; weigh 50 parts by weight of nickel powder, add 0.02 parts by weight of phosphorus pentoxide, grind for 1 hour, then add 1 times the weight of phosphorus powder at 80°C hot water, react for 1 hour, put it in a blender and mix it with 1 part by weight of silicon dioxide with a particle size of less than 300 mesh, and stir it at a speed of 300r / min for 2 hours to obtain a nickel-coated powder with a surface coated with silicon dioxide;
[0072] S3. The iron-coated powder and the nickel-coated powder in S2 are mixed evenly, dried, and 0.5 parts by weight of zinc stearate are added, and then placed in an automatic dry powder molding hydraulic press at a molding pressure of 18t / cm 2 Under the condition of , the pressure is maintained for 4s to make the blank magnetic powder core;
[0073] S4. The blank magnetic powder core formed in S3 is heat-treated at 600°C for 3 hours under nitrogen protection to obtain an iron-nickel magnetic powder core.
[0074] Performance Testing:
[0075] Specific detection method: According to standard SJ20966-2006, the performance of the iron-nickel magnetic powder cores prepared in Examples 1-3 and Comparative Examples 1-4 was detected using an IWATSUB-H analyzer (SY-8219). The results are shown in Table 1.
[0076] Table 1 Test results
[0077]
[0078] It can be seen from the test results in Table 1 that the iron-nickel magnetic powder cores prepared by the coating methods of Examples 1-3 of the present invention have high magnetic permeability, low loss and excellent comprehensive performance.
[0079] By comparing the results of Example 1 and Comparative Example 1, it can be seen that when the sulfur content of the iron powder in Comparative Example 1 is too high, its saturation magnetic flux density and magnetic permeability are worse than those in Example 1, and the hysteresis loss is also greater.
[0080] It can be seen from the results of comparative example 1 and comparative example 2 that when silicon dioxide is not pre-coated, the comprehensive performance is worse than that of example 1.
[0081] From the results of Example 1 and Example 3, it can be seen that although silica coating is also used in Example 3, it is coated after the iron-nickel powder is mixed. Although the performance is better than that without silica coating, it is still worse than the iron-nickel magnetic powder core obtained by first coating iron and nickel separately and then mixing them in the present invention.
[0082] It can be seen from the results of comparative example 1 and comparative example 4 that when no epoxy-modified silicone resin is used for coating, the neutralization performance is significantly worse than that of example 1.
[0083] In summary, the present invention uses iron-nickel raw materials with low sulfur content, and mixes them in proportion after coating with silicon dioxide respectively, and then coats them with epoxy-modified silicone resin, thereby improving the resistivity and heat resistance, and the coating is uniform and has good thermal stability. The obtained iron-nickel magnetic powder core has the characteristics of low loss and high magnetic permeability.
[0084] Finally, it should be emphasized that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A low-loss iron-nickel magnetic powder core composite coating method, characterized in that: The specific steps include: S1. Place the iron ingot and the nickel ingot in a medium frequency induction furnace for smelting, remove impurities, use spray crushing to make powder, and then sieve them according to the particle size of 150-300 mesh for use; wherein, after removing impurities, the sulfur content in the iron is less than 0.01%; S2. Weigh 50-55 parts by weight of iron powder and 45-50 parts by weight of nickel powder in S1 separately for surface treatment, and then put them into a blender and mix them with 1-1.5 parts by weight of silicon dioxide, stir for 1-2h, and obtain iron-coated powder and nickel-coated powder with silicon dioxide coated on the surface; wherein the surface treatment method is: add 0.03-0.04% of phosphorus pentoxide to the iron powder or nickel powder, grind for 1-2h, and then add 10-50 times the weight of phosphorus pentoxide hot water, react for 0.5-1h to obtain; S3. The iron-coated powder and the nickel-coated powder in S2 are mixed evenly, and then 3-4 parts by weight of a mixed solution of epoxy-modified silicone resin are added, stirred evenly, and dried to obtain an insulating coated iron-nickel magnetic powder; the mixed solution of the epoxy-modified silicone resin is 100 parts by weight of epoxy-modified silicone resin, 20-40 parts by weight of mica powder, 20-50 parts of silicon powder and 0-50 parts of titanium dioxide are added, and the mixture is ground with a grinder for 1-2h; the solid content of the epoxy-modified silicone resin is 52-58%; the epoxy-modified silicone resin is obtained by E-20 epoxy resin and dimethyldiethoxysilane in a weight ratio of 1:0.3-0.5; S4. Add lubricant to the iron-nickel magnetic powder coated with insulation in S3 and put it into the automatic dry powder forming hydraulic press. 2 Under the condition of , the pressure is maintained for 2-4s to make a blank magnetic powder core; S5. The blank magnetic powder core formed in S4 is heat treated at 600-700° C. for 2-3 hours under nitrogen protection to obtain an iron-nickel magnetic powder core.
2. The low-loss iron-nickel magnetic powder core composite coating method according to claim 1, characterized in that: In S2, the particle size of the silicon dioxide is less than 300 mesh, and the stirring speed is 300-500 r / min.
3. The low-loss iron-nickel magnetic powder core composite coating method according to claim 1, characterized in that: In S4, the lubricant is one of zinc stearate or amide wax, and the amount used accounts for 0.4-0.8% of the total amount of the insulating coated iron-nickel magnetic powder.
Citation Information
Patent Citations
Preparation method of Fe-based metal soft magnetic powder core
CN105185560A
Insulation method for improving oxidation resistance of metal magnetic powder core and material thereof
CN111192757A
Cited By
Preparation method of magnetic powder core with low loss and high direct current superposition characteristic
CN116053018A